2016
DOI: 10.1016/j.neuroimage.2016.02.060
|View full text |Cite
|
Sign up to set email alerts
|

ICA-derived cortical responses indexing rapid multi-feature auditory processing in six-month-old infants

Abstract: The abilities of infants to perceive basic acoustic differences, essential for language development, can be studied using auditory event-related potentials (ERPs). However, scalp-channel averaged ERPs sum volume-conducted contributions from many cortical areas, reducing the functional specificity and interpretability of channel-based ERP measures. This study represents the first attempt to investigate rapid auditory processing in infancy using independent component analysis (ICA), allowing exploration of sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 61 publications
0
55
0
Order By: Relevance
“…The use of independent component analysis (ICA) in EEG has evolved from a technique oriented to help in artifact detection and correction [76,77], to identify neural process and biomarkers [27,33,78,79]. Using recordings obtained at rest in 144 subjects, Congedo et al [80] reported seven sources distributed across the cortex, where three of them were also related to the Precuneus, that would serve to assessment and diagnosis of abnormal brain functioning.…”
Section: Discussionmentioning
confidence: 99%
“…The use of independent component analysis (ICA) in EEG has evolved from a technique oriented to help in artifact detection and correction [76,77], to identify neural process and biomarkers [27,33,78,79]. Using recordings obtained at rest in 144 subjects, Congedo et al [80] reported seven sources distributed across the cortex, where three of them were also related to the Precuneus, that would serve to assessment and diagnosis of abnormal brain functioning.…”
Section: Discussionmentioning
confidence: 99%
“…To compensate for the low dimensionality inherent to dipole coordinates and increase their influence on the k ‐means solution, clustering dimensions corresponding to dipole coordinates were multiplied by a factor of five (cf. Gramann et al, ; Piazza et al, ; Rapela et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous EEG study (Piazza et al, 2016b) of the cortical correlates of multi-feature rapid auditory processing in 6-monthold infants, decomposition by independent component analysis (ICA) of the whole EEG records identified the presence of a relatively large number of near bilaterally symmetric independent component (IC) processes indicating a bilaterally synchronous cortical activity (Piazza et al, 2016a). The present report aims to better investigate bilateral synchronicity by comparing infant and adult EEG data recorded using the same protocol, to assess whether brain EEG activity in infants may indeed exhibit more bilateral synchronicity at the cortical effective source level than in the adult brain.…”
Section: Introductionmentioning
confidence: 94%
“…Thirty-four typically developing infants (16 males and 18 females; age in months M = 6.4, SD = 0.4) were included in the present study. The infant group is the same that took part in the study presented in Piazza et al (2016b). Infants were included in the study if: (1) both parents were native-Italian speakers, (2) gestational age was ≥ 37 weeks, (3) birth-weight was ≥ 2500 g, (4) APGAR scores at birth at 1'and at 5'were ≥ 8, (5) infants did not have a history of hearing impairments and passed the hearing screening at birth, (6) infants and their first-degree relatives did not have certified diagnosis of neurodevelopmental or neurological disorders, and (7) the cognitive subscale of the Bayley Scales of Infant Development (Bayley, 1993) was ≥ 7.…”
Section: Participantsmentioning
confidence: 99%